Kallikrein‐binding protein inhibits LPS‐induced TNF‐α by upregulating SOCS3 expression1. Issue 5 (14th March 2013) - Dai, Zhiyu; Lu, Lei; Yang, Zhonghan; Mao, Yuling; Lu, Juling; Li, Cen; Qi, Weiwei; Chen, Yifei; Yao, Yachao; Li, Lei; Chen, Shaobo; Zhang, Yang; et al.
Abstract Kallikrein‐binding protein (KBP) was previously identified as a serpin family member with specific inhibitory effect on tissue kallikrein and angiogenesis, while there is little knowledge about the effects on inflammation. The aim of this study is to investigate whether KBP can suppress LPS‐induced inflammatory process. Our results showed that both recombinant KBP and KBP overexpression inhibited LPS‐stimulated TNF‐α transcription and translation in macrophage cell line RAW264.7 and primary macrophages. Furthermore, KBP treatment protected mice from endotoxin shock and repressed serum TNF‐α production, increasing survival rate of mice from 10% to 50% when compared to LPS alone. Moreover, qPCR and Western blot analysis demonstrated that both suppressor of cytokine signaling 3 (SOCS3) transcription and translation were induced by KBP treatment in the present of LPS. RNA interference assay and luciferase assay showed that SOCS3 was responsible for the down‐regulation of TNF‐α by KBP, rather than NF‐κB subunit p65 and β‐catenin. Therefore, we demonstrated that KBP suppressed LPS‐induced TNF‐α production via upregulating SOCS3 expression. These results present the protective effects of KBP on LPS‐induced inflammation and provide novel information for the anti‐inflammation mechanism. J. Cell. Biochem. 114: 1020–1028, 2013. © 2012 Wiley Periodicals, Inc.